2006
DOI: 10.1177/1358863x06074828
|View full text |Cite
|
Sign up to set email alerts
|

Limb hemodynamics are not predictive of functional capacity in patients with PAD

Abstract: improvements in ankle pressures, CBF, and symptoms. 5 Moreover, the approach toward development of novel treatments, such as therapeutic angiogenesis, is Abstract: To the practicing clinician, it seems obvious that limb hemodynamics would be the primary determinant of walking distance. However, other determinants, such as skeletal muscle metabolism, may play a role. Accordingly, in the current study, we examined the relationship between measures of limb hemodynamics and walking capacity in patients with periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 36 publications
(33 reference statements)
5
59
0
2
Order By: Relevance
“…Magnetic resonance imaging-based measurement of calf blood flow was moderately related to walking distance, 43 but plethysmography-based calf blood flow showed no association with treadmill walking or change in walking time. 42 Prospective studies confirm that individuals with an abnormal ABI have a greater decline in walking ability at 2-year follow-up. 44 However, the association between the magnitude of the reduction in ABI and functional outcomes is less clear.…”
Section: Impaired Angiogenesis and Reduced Microcirculatory Flowmentioning
confidence: 88%
See 1 more Smart Citation
“…Magnetic resonance imaging-based measurement of calf blood flow was moderately related to walking distance, 43 but plethysmography-based calf blood flow showed no association with treadmill walking or change in walking time. 42 Prospective studies confirm that individuals with an abnormal ABI have a greater decline in walking ability at 2-year follow-up. 44 However, the association between the magnitude of the reduction in ABI and functional outcomes is less clear.…”
Section: Impaired Angiogenesis and Reduced Microcirculatory Flowmentioning
confidence: 88%
“…7, 39 Yet some studies have shown just modest correlation between ABI and walking ability, 40,41 and other studies have found no association between ABI and the magnitude of functional limitation. 42 Limb blood flow, assessed by other techniques, has shown inconsistent associations with functional measures. Magnetic resonance imaging-based measurement of calf blood flow was moderately related to walking distance, 43 but plethysmography-based calf blood flow showed no association with treadmill walking or change in walking time.…”
Section: Impaired Angiogenesis and Reduced Microcirculatory Flowmentioning
confidence: 99%
“…Based on preliminary histologic analysis, it is also unlikely that femoral artery ligation was a less severe ischemic insult compared with YNG mice (data not shown). This leads us to hypothesize that the decrease from baseline is multifactorial and may indicate limited NOmediated vasodilation or metabolic adaptation (33). In future murine or human studies, the methodology presented herein may be sensitive enough to define the physiologic relevance of this portion of the RH response, as has been attempted for TTP and PH (15,20).…”
Section: Discussionmentioning
confidence: 99%
“…In studies of PAD patients not receiving revascularization, ABI, a measure integrating the impact of all stenoses in a limb, is poorly associated with function. 44,45 Although measures of plaque burden correlate with walking distance, 46,47 improvement in function occurs with exercise training despite no change in ABI. 23,28,48 Other factors such as the development of collaterals and improvements in endothelial function and skeletal muscle bioenergetics may maintain function in the presence of arterial restenosis or occlusion.…”
Section: Anatomic End Pointsmentioning
confidence: 99%